2020
DOI: 10.1101/2019.12.31.892091
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell shape, and not 2D migration, predicts ECM-driven 3D cell invasion in breast cancer

Abstract: Metastasis, the leading cause of death in cancer patients, requires the invasion of tumor cells through the stroma in response to migratory cues, such as those provided by the extracellular matrix (ECM). Recent advances in proteomics have led to the identification of hundreds of ECM proteins which are more abundant in tumors relative to healthy tissue. Our goal was to develop a pipeline to easily predict which of these ECM proteins is more likely to have an effect on cancer invasion and metastasis. We evaluate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…However, like A375 cells, a higher fraction of MDA-MB-231 cells that underwent constricted migration for 10 rounds (Bottom-5) showed elongated cell bodies and further elongation of their nuclei compared with Control or Bottom-12 (Fig EV2C -E). These observations coincide with previous reports that elongated cell and nuclear shape correlated with higher migration propensity in MDA-MB-231 cells (Baskaran et al, 2020). As in A375 cells, the increased migratory efficiency of MDA-MB-231 Bottom-5 cells was not related to a change in overall Lamin A/C or H3K9me3 protein levels (Fig EV2H-I).…”
Section: Nucleus Morphology Differences Associate With Redistribution...supporting
confidence: 92%
“…However, like A375 cells, a higher fraction of MDA-MB-231 cells that underwent constricted migration for 10 rounds (Bottom-5) showed elongated cell bodies and further elongation of their nuclei compared with Control or Bottom-12 (Fig EV2C -E). These observations coincide with previous reports that elongated cell and nuclear shape correlated with higher migration propensity in MDA-MB-231 cells (Baskaran et al, 2020). As in A375 cells, the increased migratory efficiency of MDA-MB-231 Bottom-5 cells was not related to a change in overall Lamin A/C or H3K9me3 protein levels (Fig EV2H-I).…”
Section: Nucleus Morphology Differences Associate With Redistribution...supporting
confidence: 92%
“…A key in vitro model system for studying the combined effects of cell-cell and cell-ECM interactions on tissue behavior is a tissue spheroid embedded in a collagen network. It has been shown that tensile forces and stiffer collagen fibers in the ECM facilitate tumor invasion [16,17], and that as various ECM proteins are modified, cell shapes may be a good predictor of invasion potential [18].…”
mentioning
confidence: 99%